Pilot Study to Evaluate the Efficacy of Polynucleotide Sodium Compared to Sodium Hyaluronate and Crosslinked Sodium Hyaluronate in Patients with Knee Osteoarthritis - Kim, Ji Yeong (J Clin Med, 2021)
Degenerative arthritis of the knee joint has become a major social problem worldwide due to population aging. There are several treatment options for knee osteoarthritis, and the intraarticular injection of sodium hyaluronate is commonly selected by many clinicians as a nonsurgical treatment. However, the efficacy of the treatment is controversial. In this pilot study, we aimed to compare polynucleotide sodium (Conjuran(®)) with sodium hyaluronate (Hyruan Plus(®)) and 1,4-butanediol diglycidyl ether-crosslinked sodium hyaluronate (Synovian(®)) in terms of analgesic efficacy after intraarticular injection in patients with knee osteoarthritis. One of the three intraarticular agents was selected according to what agents were available for outpatients when each patient was enrolled in the study. The 15 enrolled patients were subdivided into 3 groups of 5 patients each. Three injections were performed under ultrasound guidance at a 1-week intervals over a total of 3 weeks. The visual analog scale (VAS) score, the Korean version of the Western Ontario and McMaster Universities Arthritis Index (K-WOMAC), the EuroQol five-dimension scale (EQ-5D) score, and the Korean version of the painDETECT Questionnaire (K-PDQ) score were evaluated before injection and at 1, 2, and 6 weeks after the start of the treatment protocol. The primary endpoint was the change in weight-bearing pain at 4 weeks after the last injection. Secondary endpoints included pain at rest and during walking and the K-WOMAC, EQ-5D, and K-PDQ scores. Weight-bearing pain decreased significantly more from pretreatment to 6 weeks after the start of the treatment protocol in the polynucleotide sodium-treated patients than in the patients who were treated with other agents (p = 0.006, one-way ANOVA). There were no significant between-group differences in the other secondary endpoints. No adverse events occurred. In conclusion, polynucleotide sodium could effectively reduce weight-bearing pain in the patients with knee osteoarthritis compared to standard hyaluronic acid viscosupplementation.